Foraging decisions underlying restricted space use: effects of fire and forage maturation on large herbivore nutrient uptake - Raynor, Edward J.; Joern, Anthony; Nippert, Jesse B.; Briggs, John M. (My University, 2017)
Recent models suggest that herbivores optimize nutrient intake by selecting patches of low to intermediate vegetation biomass. We assessed the application of this hypothesis to plains bison (Bison bison) in an experimental grassland managed with fire by estimating daily rates of nutrient intake in relation to grass biomass and by measuring patch selection in experimental watersheds in which grass biomass was manipulated by prescribed burning. Digestible crude protein content of grass declined linearly with increasing biomass, and the mean digestible protein content relative to grass biomass was greater in burned watersheds than watersheds not burned that spring (intercept; F1,251 = 50.57, P < 0.0001). Linking these values to published functional response parameters, ad libitum protein intake, and protein expenditure parameters, Fryxell's (Am. Nat., 1991, 138, 478) model predicted that the daily rate of protein intake should be highest when bison feed in grasslands with 400–600 kg/ha. In burned grassland sites, where bison spend most of their time, availability of grass biomass ranged between 40 and 3650 kg/ha, bison selected foraging areas of roughly 690 kg/ha, close to the value for protein intake maximization predicted by the model. The seasonal net protein intake predicted for large grazers in this study suggest feeding in burned grassland can be more beneficial for nutrient uptake relative to unburned grassland as long as grass regrowth is possible. Foraging site selection for grass patches of low to intermediate biomass help explain patterns of uniform space use reported previously for large grazers in fire-prone systems. © 2016 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.
Citation: Raynor, E. J., Joern, A., Nippert, J. B., & Briggs, J. M. (2016). Foraging decisions underlying restricted space use: effects of fire and forage maturation on large herbivore nutrient uptake. Ecology and Evolution, 6(16), 5843-5853. doi:10.1002/ece3.2304
Keywords: Ecosystem Interactions; Fire; Grazing; Konza Prairie Biological Station; Mesic Tallgrass Prairie; Patch Selection